(untitled) (Brazilian Journal of Police Sciences, 2022)
Security intelligence is an important tool for knowlesge creation and sharing inside and between law enforcement agencies. Recently, brazilian government instituted the National Public Security Intelligence Policy (PNISP) and the National Public Security Intelligence Strategy (ENISP). Research carried out in companies revealed that an effective knowledge management is associated to organizational capabilities related to infraestructure (structure, technology and culture) and to processes (knowledge acquisition, conversion, application and protection). Therefore, this research seeks to verify if that norms have elements related to this capabilities, using, for this purpose, content analysis method. As main conclusions, was observed that PNISP and ENISP have in their content elements related to that capabilities, with grater atention in the organizational structure and the knowledge acquisition process.